2015
DOI: 10.1002/jcp.25238
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Human Polyomavirus BK and Hypoxia Inducible Factor‐1 alpha

Abstract: BK polyomavirus (BKV) has a worldwide seroprevalence of approximately 90%. After primary infection, BKV establishes a life-long latency within the urogenital tract. The severe immunological impairment occurring in renal transplant recipients leads to BKV reactivation, which may result in polyomavirus associated nephropathy (PVAN). While the transplanted kidney is transiently unperfused, Hypoxia Inducible Factors (HIFs) mediate the cellular response to hypoxia. The α-subunit of HIF isoform 1 (HIF-1α) may intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…HIF-1 activation is a general phenomenon in human infectious diseases caused by hypoxia-dependent mechanisms (Werth et al, 2010). However, an earlier study suggested that HIF-1α binds to the BK polyomavirus promoter and increases the amount of BK polyomavirus DNA (Signorini et al, 2016), which indicates that virus-mediated triggering of HIF-1α might be a general phenomenon. This is the first report to indicate that ARV σA upregulates HIF-1α through activation of two distinct pathways.…”
Section: Discussionmentioning
confidence: 97%
“…HIF-1 activation is a general phenomenon in human infectious diseases caused by hypoxia-dependent mechanisms (Werth et al, 2010). However, an earlier study suggested that HIF-1α binds to the BK polyomavirus promoter and increases the amount of BK polyomavirus DNA (Signorini et al, 2016), which indicates that virus-mediated triggering of HIF-1α might be a general phenomenon. This is the first report to indicate that ARV σA upregulates HIF-1α through activation of two distinct pathways.…”
Section: Discussionmentioning
confidence: 97%
“…While most in vitro studies on viral replication utilize cells cultured at atmospheric oxygen levels (~20% O 2 ), the vast majority of human tissues have oxygen levels much lower than this (referred to as hypoxia). Hypoxia can have opposing effects on viral proliferation, inducing the replication of Epstein–Barr virus 3 5 , Kaposi sarcoma-associated herpesvirus 4 , 6 , human T-cell leukemia virus 7 , and human polyomavirus BK 8 , while suppressing the infectivity of adenovirus 9 and Moloney murine leukemia virus 10 . These contrasting effects are likely to reflect the variable oxygen tension at the sites of virus replication and the complex interplay between viruses and their hosts 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The program of TaqMan Real Time PCR assay provides four steps: 2 min at 50°C, 15 min at 95°C followed by 40 cycles of 15 s at 95°C and 1 min at 60°C. The composition of the reaction mix, the thermal profile, the primers and the probe sequences were previously published 21–24 . The primers and probes sequences were also reported in the Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The composition of the reaction mix, the thermal profile, the primers and the probe sequences were previously published. [21][22][23][24] The primers and probes sequences were also reported in the Table 2. A quantitative Real-Time PCR targeting the β-globin gene was conducted to calculate the percentage of the infected cells, as previously described.…”
Section: Study Populationmentioning
confidence: 99%